The Impact of Financial Performance and Stakeholder Pressure on Sustainability Report Disclosure: The Moderating Role of Independent Commissioners - Herawansyah; Danang Adi Putra; Indah Oktari Wijayanti (HM Publisher, 2024)
In the contemporary business landscape, sustainability reporting has become increasingly critical as stakeholders demand greater transparency and accountability from companies regarding their environmental, social, and governance (ESG) performance. This study delves into the factors that influence the extent of sustainability report disclosure, focusing on the role of financial performance, stakeholder pressure, and the moderating effect of independent commissioners. This study employs a quantitative approach, utilizing data from 96 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The sample encompasses 288 observations, and purposive sampling was employed to select companies that met specific criteria, ensuring the inclusion of companies that have consistently disclosed sustainability reports and maintained financial stability. Regression analysis with an absolute difference test was conducted using SPSS 23 to analyze the relationships between the variables. The findings of this study indicate that financial performance and stakeholder pressure significantly influence sustainability report disclosure. Companies with higher financial performance tend to disclose more sustainability information, suggesting that they have the resources and motivation to invest in sustainability reporting. This positive association between financial performance and sustainability reporting implies that companies with stronger financial positions are better equipped to allocate resources towards sustainability initiatives and their subsequent disclosure. In conclusion, the proportion of independent commissioners on the board moderates these relationships, indicating that independent oversight enhances the positive effects of financial performance and stakeholder pressure on sustainability report disclosure. The presence of independent commissioners on the board strengthens corporate governance mechanisms, ensuring greater transparency and accountability in sustainability reporting.